From Mindset to Market: Analyzing the Relationship Between Entrepreneurial Attitudes and Career Intentions - Ballad, Sheryll Joy R. (Research and Advances in Education, 2026)
The research looks at the psychological and social influences on Filipino students’ transition into the entrepreneurial realm. The foundation of this study is the Theory of Planned Behavior (TPB), which examines how personal motivations (self-fulfillment, autonomy, and risk tolerance) combine with external sources of support (family, friends, and social status) to shape an individual’s aspirations for a career in entrepreneurship. The research employs a correlational design and quantitative methods, surveying Hospitality Management students at Northeastern College (Santiago City, Philippines). The following findings indicate a statistically significant positive correlation between entrepreneurial attitudes and the intention to pursue a career in entrepreneurship within 5 years of graduating. Although respondents have a medium level of psychological intent to pursue entrepreneurship, their advanced progression into entrepreneurship will be significantly influenced by subjective norms and perceived social support. Personal fulfillment and autonomy were found to be stronger intrinsic motivators for pursuing entrepreneurship than financial reward. The findings suggest that to assist young people in closing the intentions-action gap, educational curricula and policies should promote self-efficacy and develop structured “if-then” plans for implementation.